Solid Lipid Curcumin Particles Induce More DNA Fragmentation and Cell Death in Cultured Human Glioblastoma Cells than Does Natural Curcumin. (19th November 2017) - Maiti, Panchanan; Al-Gharaibeh, Abeer; Kolli, Nivya; Dunbar, Gary L.
Abstract : Despite recent advancements in cancer therapies, glioblastoma multiforme (GBM) remains largely incurable. Curcumin (Cur), a natural polyphenol, has potent anticancer effects against several malignancies, including metastatic brain tumors. However, its limited bioavailability reduces its efficiency for treating GBM. Recently, we have shown that solid lipid Cur particles (SLCPs) have greater bioavailability and brain tissue penetration. The present study compares the efficiency of cell death by Cur and/or SLCPs in cultured GBM cells derived from human (U-87MG) and mouse (GL261) tissues. Several cell viability and cell death assays and marker proteins (MTT assay, annexin-V staining, TUNEL staining, comet assay, DNA gel electrophoresis, and Western blot) were investigated following the treatment of Cur and/or SLCP (25 μ M) for 24–72 h. Relative to Cur, the use of SLCP increased cell death and DNA fragmentation, produced longer DNA tails, and induced more fragmented nuclear lobes. In addition, cultured GBM cells had increased levels of caspase-3, Bax, and p53, with decreases in Bcl2, c-Myc, and both total Akt, as well as phosphorylated Akt, when SLCP, rather Cur, was used. Our in vitro work suggests that the use of SLCP may be a promising strategy for reversing or preventing GBM growth, as compared to using Cur.